The effective methods of teaching Chinese literature - Madiyev D. А. (Journal of Oriental Studies, 2016)
In this article considers the most effective methods of Chinese literature teaching on the example of Kazakh National university’s faculty of Oriental studies and also there is given the row of offers on students self studying.